2019
DOI: 10.1371/journal.pone.0223514
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of midkine on hepatocellular carcinoma: A meta-analysis

Abstract: ObjectiveTo evaluate the dependability and accuracy of midkine (MK) in the diagnosis of hepatocellular carcinoma (HCC).MethodsPubMed, EMBASE, Web of Science, China Biology Medicine disc and grey literature sources were searched from the date of database inception to January 2019. Two authors (B-H.Z. and B.L.) independently extracted the data and evaluated the study quality using the Quality Assessment of Diagnostic Accuracy Studies-2 tool. The sensitivity, specificity, positive likelihood ratio (LR+) and negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Derivation of PLSec as a blood-based long-term HCC risk biomarker Our computational pipeline identified 43 candidate serum proteins for which validated antibodies are available for quantitative multiplex assessment (Figure 1). This preliminary panel included proteins that were previously reported as potential HCC risk biomarkers(e.g., interleukin-6 [IL-6], osteopontin, and midkine), [14][15][16] supporting the validity of our unbiased secretome biomarker derivation pipeline. Based on the association with the prognostic tissue transcriptome and the least information redundancy among the probes in the optimization set, we ultimately selected 6 highrisk-associated serum proteins, including vascular cell adhesion molecule 1 (VCAM-1), insulin-like growth factor-binding protein 7 (IGFBP-7), gp130, matrilysin, IL-6, and C-C motif chemokine ligand 21 (CCL-21), and 2 low-risk-associated serum proteins, angiogenin and protein S. We observed high within-plate reproducibility (r 2 = 0.9997, p = 1.1 3 10 À11 ), inter-plate/batch reproducibility (r 2 = 0.971, p = 7.7 3 10 À6 ) of technical replicates, and sensitivity for positive control proteins (99.9% G 2.5%), supporting the assay reliability as a clinical test.…”
Section: Resultsmentioning
confidence: 63%
“…Derivation of PLSec as a blood-based long-term HCC risk biomarker Our computational pipeline identified 43 candidate serum proteins for which validated antibodies are available for quantitative multiplex assessment (Figure 1). This preliminary panel included proteins that were previously reported as potential HCC risk biomarkers(e.g., interleukin-6 [IL-6], osteopontin, and midkine), [14][15][16] supporting the validity of our unbiased secretome biomarker derivation pipeline. Based on the association with the prognostic tissue transcriptome and the least information redundancy among the probes in the optimization set, we ultimately selected 6 highrisk-associated serum proteins, including vascular cell adhesion molecule 1 (VCAM-1), insulin-like growth factor-binding protein 7 (IGFBP-7), gp130, matrilysin, IL-6, and C-C motif chemokine ligand 21 (CCL-21), and 2 low-risk-associated serum proteins, angiogenin and protein S. We observed high within-plate reproducibility (r 2 = 0.9997, p = 1.1 3 10 À11 ), inter-plate/batch reproducibility (r 2 = 0.971, p = 7.7 3 10 À6 ) of technical replicates, and sensitivity for positive control proteins (99.9% G 2.5%), supporting the assay reliability as a clinical test.…”
Section: Resultsmentioning
confidence: 63%
“…A study by Zhang et al reported that midkine has a sensitivity of 85% and specificity of 83% in diagnosing HCC. This result was reported at a cut-off value of >0.5 ng/mL [34]. Another systematic review found that midkine is more superior compared to AFP in detecting HCC.…”
Section: Discussionmentioning
confidence: 71%
“…Midkine, a protein-secreting cytokine that is highly expressed in inflammation and cell proliferation, can be a diagnostic marker [29]. Detection of overexpressed Midkine in blood serum or plasma would adequately serve as early malignancy screening [30]. Previous studies observed that serum Midkine measures have higher sensitivity in the early stages of HCC than often-used measures [31].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that MDK also plays a role in the occurrence, development, metastasis, and prognosis of liver cancer ( Muramatsu, 2010 ). Further more, some studies have found that the sensitivity of MDK for the diagnosis of HCC could reach 85% through meta-analysis ( Zhang et al, 2019 ), and other studies have shown that the sensitivity can reach more than 80% in the early stages of liver cancer and AFP-negative liver cancer ( Luo et al, 2020 ). In addition, many liver cancers are associated with HBV and HCV infections, and it has been suggested that MDK may have an impact on hepatitis-associated HCC ( Lu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%